Bacteria-propelled microtubular motors for efficient penetration and targeting delivery of thrombolytic agents. (1st April 2022) - Xie, Songzhi; Mo, Chuanfei; Cao, Wenxiong; Xie, Shuang; Li, Shang; Zhang, Zhanlin; Li, Xiaohong
Abstract: Effective thrombolysis is critical to rapidly rebuild blood flow for thrombosis patients. Drug delivery systems have been developed to address inadequate pharmacokinetics of thrombolytic agents, but challenges still remain in the timely removal of blood clots regarding the dense fibrin networks. Herein, rod-shaped tubular micromotors were developed to achieve efficient penetration and thorough destruction of thrombi. By using electrospun fiber fragments as the template, urokinase (uPA)-loaded polydopamine (PDA) microtubes with surface decorated fucoidan ( Fu PDAuPA ) were prepared at the aspect ratio of around 2. One E. coli Nissle 1917 (EcN) was assembled into one microtube to construct a Fu PDAuPA @EcN hybrid micromotor through PDA adhesion and L-aspartate induction. The pharmacokinetic analysis indicates that the encapsulation of uPA into micromotors extends the half-life from 0.4 to 5.6 h and increases the bioavailability over 10 times. EcN-propelled motion elevates adsorption capacities of Fu PDAuPA @EcN for more than four times compared with that of Fu PDAuPA . The fucoidan-mediated targeting causes 2-fold higher thrombolysis capacity in vitro and over 10-fold higher uPA accumulation in thrombi in vivo . In the treatment of venous thrombi at mouse hindlimbs, intravenous administration of Fu PDAuPA @EcN completely removed blood clots with almost full recovery of blood flows and apparently alleviated tail bleeding. It should be noted that Fu PDAuPA @EcN treatment at a reduced uPA dose caused no significant difference in the blood flow rate compared with those of Fu PDAuPA . The synergistic action of fucoidan-induced targeting and EcN-driven motion provides a prerequisite for promoting thrombolytic efficacy and reducing uPA dose and bleeding side effect. Statement of significance: The standard treatment to thrombosis patient is intravenous infusion of thrombolytic agents, but the associated bleeding complications and impairment of normal haemostasis greatly offset the therapeutic benefits. Drug delivery systems have been developed to address the limitations of inadequate pharmacokinetics of thrombolytic agents, but challenges still exist in less efficient penetration into dense networks for thorough destruction of thrombi. Up to now only few attempts have been made to construct nano-/micromotors for combating thrombosis and there is no single case that antithrombosis is assisted by bacteria or cells-propelled motors. Herein, bacteria-propelled microtubes were developed to carry urokinase for efficient penetration into blood clots and effective thrombolysis. The synergistic action of bacteria-driven motion and specific ligand-induced targeting holds a promising treatment strategy for life-threatening cardiovascular diseases such as thrombosis and atherosclerosis. Graphical abstract: Image, graphical abstract